Differences in the Morphological Characteristics and Body Composition of Handball Players WHC Levalea in Montenegro and WHC Grude in Bosnia and Herzegovina - Marina Vukotic; Marin Corluka; Ivan Vasiljevic; Marija Bubanja (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of this research was to determine the differences in the level of anthropometric characteristics and body composition among the top handball players of WHC Levalea from Niksic and WHC Grude from Grude.The sample of respondents consists of 25 top-ranked senior players from the First Handball League of Montenegro and handball Premier League of Bosnia and Herzegovina, divided into two sub-assignments. The first subunit was played by 11 players from WHC Levalea from Niksic, an average age of 16.64, who finished as women's vice-champions League of Montenegro and 14 player WHC Grude from Grude, an average of 20.35, which are the current championship handball Premier League of Bosnia and Herzegovina. Morphological characteristics in the body composition were evaluated by a battery of 11 variables: body height, body weight, body mass index, fat percentage, muscle mass, bone mass, waist size, triceps skin set, biceps skin set, back skin set and abdominal skin set. The standard central and dispersive parameters of all variables were calculated. The significance of the differences between the players of the top two handboll clubs in the morphological characteristics and variables for assessing body composition was determined by a t-test for independent samples. It has been found that the handdballeas of two mentioned clubs had statistically in two varijables that are evaiuated by the triceps skin set end biceps skin set in favor of the women´s WHC Levalea.